The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.17584/rcch.2016v10i2.5065
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades fisicoquímicas durante el crecimiento y desarrollo de frutos de lulo (Solanum quitoense Lam.)

Abstract: RESUMENEl lulo (Solanum quitoense Lam.) se ha considerado frutal promisorio y especie potencial para mercados globales, constituyéndose en un renglón importante para la economía del departamento de Boyacá (Colombia). La presente investigación buscó realizar una caracterización fisicoquímica de los frutos de dos variedades de lulo (Chonto grueso y Criollo) durante su crecimiento y desarrollo, procedentes del municipio de Pachavita, Boyacá. Para ello se tomaron frutos cada 10 días, a partir de los 30 días despué… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
6
0
2
Order By: Relevance
“…This means that the maximum growth rate occurred in the second stage of development. This agrees with that observed in lulo fruits (Almanza-Merchán et al, 2016), pears (Molina-Ochoa et al, 2016) and Ultra Red Gala apples (Yuri et al, 2011). In this latter study, the AGR and RGR had similar trends to those found in cv.…”
Section: Growth Analysissupporting
confidence: 91%
“…This means that the maximum growth rate occurred in the second stage of development. This agrees with that observed in lulo fruits (Almanza-Merchán et al, 2016), pears (Molina-Ochoa et al, 2016) and Ultra Red Gala apples (Yuri et al, 2011). In this latter study, the AGR and RGR had similar trends to those found in cv.…”
Section: Growth Analysissupporting
confidence: 91%
“…The final phase is fruit ripening, generally initiated once the fruit has acquired physiological maturity, at which stage it has attained the maximum size and capability for ripening, even after detachment from the mother plant (Paliyath et al, 2019). Many fruits show a single sigmoid growth phase such as lulo fruit (Almanza-Merchán et al, 2016), while others exhibit double or multiphasic growth patterns (Paliyath et al, 2019), like grapevine fruit (Almanza-Merchán et al, 2012).…”
Section: Fruitsmentioning
confidence: 99%
“…Many fruit trees have their origin in the Andean areas (Ligarreto, 2012), especially numerous Solanaceous species (Blancke, 2016;Criollo et al 2017). Solanaceae is one of the main families of economically important plants in Colombia (Torres-González, 2019;Almanza-Merchán et al 2016). These are the plants of indeterminate growth, that is, flowering, fruiting, and vegetative growth occur at the same time (Fischer et al 2011).…”
Section: Introductionmentioning
confidence: 99%